Antioxidant activities of curry leaves (Murayya koeniigi) and salam leaves (Eugenia polyantha) - Novi Safriani; Normalina Arpi; Novia Mehra Erfiza; Rini Ariani Basyamfar (Syiah Kuala University, 2011)
This study aimed to extract the active antioxidant compounds from curry leaves (Murayya koeniigi) and salam leaves (Eugenia polyantha) using three types of solvent; water, ethanol (50%) and hexane, and determine the total polyphenols contents, activity of free radicals scavenging using DPPH (1,1-diphenyl-2-picrylhydrazyl) and ferric reducing power of the extract of those materials. The result showed that curry leaves extracted using water contain a higher amount of polyphenols than other solvent extracts, while for the salam leaves, ethanol (50%) extracts give a higher polyphenol content than others. Total polyphenols extracts had a positive correlation with antioxidant activity in both DPPH radical scavenging and ferric reducing power. Extracts that contain a high amount of polyphenols also exhibit high antioxidant activity. The result indicated that the polarity level of the solvent will determine extraction result and its antioxidant activity